2022
DOI: 10.1182/blood.2021013443
|View full text |Cite
|
Sign up to set email alerts
|

HLA informs risk predictions after haploidentical stem cell transplantation with posttransplantation cyclophosphamide

Abstract: Hematopoietic cell transplantation from HLA-haploidentical related donors is increasingly used to treat hematologic cancers; however, characteristics of the optimal haploidentical donor have not been established. We studied the role of donor HLA mismatching in graft-versus-host disease (GVHD), disease recurrence and survival after haploidentical donor transplantation with post-transplantation cyclophosphamide (PTCy) for 1434 acute leukemia or myelodysplastic syndrome patients reported to the Center for Interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 49 publications
4
54
1
3
Order By: Relevance
“…In the present study, we found that a high CF-iKIR score was associated with improved OS and PFS, this could not be merely attributed to either lower NRM (HR, 0.69; P = .079) or relapse protection (HR, 0.94; P = .79) yet the combined effects on both could explain this finding. A registry study showed that higher donor age is associated with inferior mortality in haplo-HSCT (14), and our exploratory classification and regression tree analysis, which integrated donor characteristics and CF-iKIR scores, showed that donor age <58 years combined with a CMVnonreactive recipient was associated with the best OS, whereas donor age ≥58 years was associated with the worst OS. In the rest of the cases (80% of our cohort), a high CF-iKIR score was associated with superior survival in CMV-reactive recipients whose donor was <58 years old, indicating that an interaction between donor CF-iKIR and recipient ligands may be protective against CMV reactivation.…”
Section: Discussionmentioning
confidence: 70%
“…In the present study, we found that a high CF-iKIR score was associated with improved OS and PFS, this could not be merely attributed to either lower NRM (HR, 0.69; P = .079) or relapse protection (HR, 0.94; P = .79) yet the combined effects on both could explain this finding. A registry study showed that higher donor age is associated with inferior mortality in haplo-HSCT (14), and our exploratory classification and regression tree analysis, which integrated donor characteristics and CF-iKIR scores, showed that donor age <58 years combined with a CMVnonreactive recipient was associated with the best OS, whereas donor age ≥58 years was associated with the worst OS. In the rest of the cases (80% of our cohort), a high CF-iKIR score was associated with superior survival in CMV-reactive recipients whose donor was <58 years old, indicating that an interaction between donor CF-iKIR and recipient ligands may be protective against CMV reactivation.…”
Section: Discussionmentioning
confidence: 70%
“…Post-HSCT cyclophosphamide is now the most widely used GVHDprevention strategy in haploidentical transplantation. However, it is less commonly used in patients with matched donors (33).…”
Section: Discussionmentioning
confidence: 99%
“…Moving forward, the availability of potential donors that produce similar outcomes may even allow the selection of personalized donors based on other factors that may limit relapse (eg, specific HLAs) or disease predispositions. 40 …”
Section: Discussionmentioning
confidence: 99%